Friends hold all things in common tradition, intellectual property, and the Adages of Erasmus - Eden, Kathy, 1952- (New Haven, Conn. ; London : Yale University Press, 2001)
This study of Erasmus's Adages focuses on both the commitment to friendship & common property that Erasmus shares with his favourite philosophers & the early history of private property that transforms European attitudes concerning the right to copy.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Erasmus, Desiderius, -- -1536.; Intellectual property -- History; Law; Europe; 16th century, c 1500 to c 1599.; Medieval philosophy; Methods, theory & philosophy of law; Laws of specific jurisdictions & specific areas of law